Rapidly non-ipf progressive fibrosing interstitial lung disease: a phenotype with an ipf-like behavior - Khine, Ngu (Sarcoidosis Vasc Diffuse Lung Dis, 2020)
BACKGROUND: A subgroup of patients with fibrotic ILD experience progression and several risk factors for ILD progression have been reported, such as male sex, older age, lower baseline pulmonary function, and a radiological or pathological pattern of usual interstitial pneumonia. OBJECTIVE: To describe a possible new phenotype of rapidly non IPF progressive fibrosing with an IPF-like outcome. METHODS: Three previously fit and well patients who developed a rapidly progressive ILD and died within 6 to 7 months from the initial development of respiratory symptoms. RESULTS: Unlike what is currently known, our patients developed a severe fibrosing ILD with an IPF-like outcome despite a) being younger than the average patient with IPF, b) having received a non-IPF MDT diagnosis, c) having a non-UIP pattern on HRCT. Moreover and similarly to IPF, they failed to respond to immunosuppressive treatment which is the preferred treatment option in these cases. CONCLUSION: We believe that patients who present with similar characteristics should be considered as likely to develop a phenotype of rapidly progressive ILD and be treated with antifibrotic medications instead of immunosuppressive ones according to the favourable treatment response to antifibrotic therapy observed in clinical trials of patients with progressive fibrosing ILDs. (Sarcoidosis Vasc Diffuse Lung Dis 2020; 37 (2): 231-233)